Cluster randomisation or randomised consent as an appropriate methodology for trials in palliative care: a feasibility study [ISRCTN60243484] - Finlay Ilora; Johnstone Ros; Russell Ian; Fowell Andrew; Russell Daphne (BMC Palliative Care, 2004)
Abstract Background Although guidelines for the care of the dying patient exist the evidence base to support the guidelines is poor. Some of the factors contributing to this include failure to recruit to trials, protective healthcare professionals and subsequent attrition from trials due to the death of the patients. Recent studies report favourably on the use of cluster randomisation as an appropriate methodology for use in this patient group. Methods/design A feasibility study, exploring two types of randomisation as appropriate methodology for trials involving dying patients. Cluster randomisation and randomised consent will be utilised following a crossover design at two sites, one oncology ward and one Macmillan unit within the Northwest Wales NHS Trust. All patients commencing on the Integrated Care Pathway (ICP) for the Last Days of Life will be eligible for inclusion in the study. Using the hypothesis that it is not necessary to prescribe an anti-emetic medication when setting up a syringe driver for the dying patient, the study will evaluate different models of research methodology. Discussion The identification of the most appropriate methodology for use in studies concerning this patient group will inform the development of future clinical studies. Furthermore, the outcomes of this feasibility study will inform the development, of a proposal seeking funding for Wales-wide trials in palliative care. The identification of an appropriate methodology will provide a starting point for the establishment of a robust evidence base for the care of the dying patient.